KARAKTERISTIK BAMBU ORI BANYUWANGI LAMINASI SUSUNAN LURUS BERDASARKAN KUAT TEKAN, KUAT TARIK DAN KUAT LENTUR - Mirza Ghulam Rifqi; M. Shofi'ul Amin; Riza Rahimi Bachtiar; Dadang Dwi Pranowo; Hakim Sobirin (Program Studi Teknik Sipil, Fakultas Teknik dan Perencanaan, Universitas Warmadewa, 2022)
The need for wood is increasing, it will be large-scale exploitation that destroys forest ecosystems. The use of wood materials must be reduced by replacing them with other materials so that the forest ecosystem is maintained. A suitable material to replace wood as a construction material is bamboo. Laminated bamboo is structural engineering to improve the mechanical properties of bamboo. The manufacture of laminated bamboo by gluing bamboo slats using a felt system to become blocks. In this study, using original bamboo with PVAC (Polyvinyl Acetate) adhesive. This study aims to determine the characteristics of laminated straight bamboo based on compressive strength, bending, and tensile strength. The manufacture and testing of laminated bamboo refer to SNI-03-3958-1995, SNI-03-3399-1994, SNI 03-3959-1995 and ISO 22157; 2019. The results showed that the characteristics of laminated bamboo without preservation and preservation with dimensions of 50 mm × 50 mm × 200 mm had an average compressive strength of 44.86 MPa and 40.96 MPa. While the bending value of laminated bamboo without preservation and preservation of dimensions 50 mm × 50 mm × 760 mm has an average value of bending of 85.45 MPa and 80.41 MPa. The tensile strength value of laminated bamboo without curing and preserving dimensions of 25 mm × 25 mm × 460 mm has an average of 519.95 MPa and 457.02 MPa. Based on the wood grade approach, laminated bamboo belongs to class II and belongs to the E25 quality code.